Algorithms of common solutions for a fixed point of hemicontractive-type mapping and a generalized equilibrium problem - Zegeye, Habtu; Hadush Meche, Tesfalem; Goa Sangago, Mengistu (International Journal of Advanced Mathematical Sciences, 2017)
In this paper, we introduce and study an iterative algorithm for finding a common element of the set of fixed points of a Lipschitz hemicontractive-type multi-valued mapping and the set of solutions of a generalized equilibrium problem in the framework of Hilbert spaces. Our results improve and extend most of the results that have been proved previously by many authors in this research area.
Keywords: Fixed Points of Mappings; Generalized Equilibrium Problem; Hemicontractive-type Multi-valued Mapping; Iterative Algorithm; Strong Convergence.